Obligations of Opening, Depositing, and Blocking Notary Accounts in the Implementation of Notary Positions in Banking Business - Darmini, Ninik (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021)DO - 10.24843/JMHU.2021.v10.i04.p02, 2021)
This study aims to identify and analyze the intent and purpose of the obligation to open, deposit, and freeze a Notary's account at the Bank as well as the conformity of these obligations with the cash collateral principles and the prevailing laws and regulations. This normative juridical research is descriptive with a statutory approach. This study uses secondary data which is supported by the results of interviewees. The data were analyzed qualitatively with the inductive method. In this study it was found that, firstly, there are differences in views between the Bank on the one hand and the Indonesian Notary Association (INI) and academics on the other hand on this obligation. The Bank stated this obligation for the smooth operation of the Notary's work and the principle of mutual benefit (reciprocity) of the Bank in collecting public funds. Meanwhile, the Notary sees that this obligation injures the Notary's dignity as a public official because it has the potential to eliminate the Notary's independence and professionalism, and academics see that this obligation also creates financial ties that have the potential to make the Notary take risks – including the risk of violating the law, ethics, and conscience – in addition to affecting the independence and professionalism of the Notary. Second, deposits with or without blocking a Notary's account at the Bank cannot be categorized as cash collateral because they do not meet the legality of collateral: Notaries are not bank debtors, but are general officials who assist the Bank in lending by making an authentic deed of guarantee loading. Third, deposits with or without blocking a Notary's account at the Bank are contrary to the laws and regulations governing the position of a Notary – as well as the Notary Code of Ethics – and the legal principles of guarantees.